Ligand-dependent interactions of coactivators steroid receptor coactivator-1 and peroxisome proliferator-activated receptor binding protein with nuclear hormone receptors can be imaged in live cells and are required for transcription - Llopis, Juan (The National Academy of Sciences, 2000)
Members of the nuclear receptor superfamily are thought to activate transcription by recruitment of one or more recently identified coactivator complexes. Here we demonstrate that both peroxisome proliferator-activated receptor binding protein (PBP) and steroid receptor coactivator-1 (SRC-1) are required for ligand-dependent transcription of transiently transfected and chromosomally integrated reporter genes by the estrogen receptor (ER) and retinoic acid receptor (RAR). To examine ligand-dependent interactions between nuclear receptors and specific coactivators in living cells, these proteins were tagged with cyan (CFP) and yellow (YFP) mutants of the green fluorescent protein. Fluorescence resonance energy transfer (FRET) from the CFP to the YFP indicated interaction between the receptor and coactivator. CFP fusions to RAR or its ligand-binding domain exhibited rapid ligand-dependent FRET to YFP-tagged nuclear receptor interaction domains of the coactivators SRC-1 and PBP. The ER-ligand-binding domain, unlike RAR, also exhibited some basal interaction with coactivators in unstimulated cells that was abolished by the receptor antagonists tamoxifen or ICI182,780. Inhibition of FRET by tamoxifen but not ICI182,780 could be reversed by estradiol, whereas estradiol-enhanced FRET could not be inhibited by either antagonist, indicating that ligand effects can show varying degrees of hysteresis. These findings suggest that ligand-dependent transcriptional activities of the RAR and ER require concurrent or sequential recruitment of SRC-1 and PBP-containing coactivator complexes.